2016
DOI: 10.1016/j.msec.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cathodic polarization on coating doxycycline on titanium surfaces

Abstract: Cathodic polarization has been reported to enhance the ability of titanium based implant materials to interact with biomolecules by forming titanium hydride at the outermost surface layer. Although this hydride layer has recently been suggested to allow the immobilization of the broad spectrum antibiotic doxycycline on titanium surfaces, the involvement of hydride in binding the biomolecule onto titanium remains poorly understood. To gain better understanding of the influence this immobilization process has on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 213 publications
0
1
0
1
Order By: Relevance
“…In fluoride content, DSO implants present a marginally higher percentage than an undetectable amount in STS implants; other studies also highlight the difference in contact angle between these two systems. The incorporation of fluorine is due to the hydrofluoric treatment reported in the literature. , These differences in elemental composition suggest that the two types of implants, DSO and STS, undergo different surface treatments, resulting in slightly different surface chemistries that could influence their performance and osseointegration properties in clinical applications. , It is important to note that the presence of elements such as carbon may not just indicate the elemental composition of the implant itself but also adsorbed or residual substances from the environment during handling of the implants during XPS analysis. , Conforto et al identified the SLA surface top layer as TiH 1.971 , though our electron diffraction studies could not confirm this. Similar findings have been seen by others. , XPS analysis by others found the surface to be composed of TiO 2 [7], with an oxide layer thickness of 4.5–5.5 nm, including TiO and Ti 2 O 3. Thermal desorption spectroscopy revealed significant hydrogen in the subsurface layer of SLA compared to polished surfaces .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In fluoride content, DSO implants present a marginally higher percentage than an undetectable amount in STS implants; other studies also highlight the difference in contact angle between these two systems. The incorporation of fluorine is due to the hydrofluoric treatment reported in the literature. , These differences in elemental composition suggest that the two types of implants, DSO and STS, undergo different surface treatments, resulting in slightly different surface chemistries that could influence their performance and osseointegration properties in clinical applications. , It is important to note that the presence of elements such as carbon may not just indicate the elemental composition of the implant itself but also adsorbed or residual substances from the environment during handling of the implants during XPS analysis. , Conforto et al identified the SLA surface top layer as TiH 1.971 , though our electron diffraction studies could not confirm this. Similar findings have been seen by others. , XPS analysis by others found the surface to be composed of TiO 2 [7], with an oxide layer thickness of 4.5–5.5 nm, including TiO and Ti 2 O 3. Thermal desorption spectroscopy revealed significant hydrogen in the subsurface layer of SLA compared to polished surfaces .…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings have been seen by others. 72,73 XPS analysis by others found the surface to be composed of TiO 2 [7], with an oxide layer thickness of 4.5−5.5 nm, including TiO and Ti 2 O 3. 52 Thermal desorption spectroscopy revealed significant hydrogen in the subsurface layer of SLA compared to polished surfaces.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Furthermore, polarization of the molecule (ampholyte) can be used for attachment to titanium in an electrochemical process. For example, two biomolecules, doxycycline and simvastatin, as coating candidates with such a technique have been reported [ 97 , 98 , 99 , 100 , 101 ].…”
Section: Biomoleculesmentioning
confidence: 99%
“…Однако доксици клин связывался с оксидной пленкой, которая была изменена во время электрохимического процесса. Титан с таким способом модифицированной по верхностью резко снижал колонизацию и содержа ние в культуральной среде биолюминесцентного S. epidermidis Xen43 [39].…”
Section: использование антибиотиков для профилактики периимплантитовunclassified